Seroprevalence of SARS-CoV-2 Infection in Portugal in May-July 2020: Results of the First National Serological Survey (ISNCOVID-19) - Kislaya, Irina (2021)
Introduction: The aim of this study was to estimate and describe the prevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) specific antibodies (immunoglobulin M and/or immunoglobulin G) in Portugal in May-July 2020. Material and methods: A cross-sectional seroepidemiological survey was developed after the peak of the first epidemic wave on a sample of 2301 Portuguese residents, aged 1 year or older. Survey sample was selected using a two-stage stratified non-probability sampling design (quota sampling). SARS-CoV-2 immunoglobulin M and immunoglobulin G antibodies were measured in serum samples by enzyme-linked immunosorbent assay. Seroprevalence estimates of immunoglobulin M and/or immunoglobulin G and 95% confidence intervals were stratified by sex, age group, health region and education. Results: Overall, seroprevalence was 2.9% (95% confidence interval: 2.0% - 4.2%). Higher prevalence rates were observed in male (4.1%, 95% confidence interval: 2.6% - 6.6%) and those with secondary education (6.4%, 95% confidence interval: 3.2% - 12.5%). Differences in seroprevalence by age group and region were not statistically significant. Discussion: The estimated seroprevalence of SARS-CoV-2 was higher than the cumulative incidence reported by the National Surveillance System but far from necessary to reach herd immunity. Conclusion: Our results support limited extent of infection by SARS-CoV-2 in the study population possibly due to early lockdown measures implemented in Portugal and support the need to continue monitoring of SARS-CoV-2 seroprevalence in order to increase our knowledge about the evolution of the epidemic and to estimate the proportion of the susceptible population over time.